Pembuatan minyak plastik dengan proses pirolisis - Chalilullah Rangkuti; Tono Sukarnoto; Muhammad Rijani (Badan Kerja Sama Teknik Mesin Indonesia, 2019)
Especially at this time in big cities like jakarta is certainly a lot of society for various commodities every day .Similarly , the amount of waste generated every day reaches Â± 6000 tons which is dumped into bantar gebang tpu , and among of the waste 13 % -14 % is plastic type , not to mention not picked up by scavengers .It is better to use this waste to be a useful compared to the habits of people who as often as burn garbage .Burning waste will make water pollution especially if plastic waste .In this study made fuel oil sourced from plastic using gasification and distillation method that will convert gas from plastic into oil .From the results of this study found that the resulting plastic oil is close to the an element of of diesel oil .The amount of oil produced from each kg of plastic raw material produced 570 ml of plastic oil .This oil is close to the type of diesel oil